2004
DOI: 10.1002/bem.10165
|View full text |Cite
|
Sign up to set email alerts
|

Cellular phone use does not acutely affect blood pressure or heart rate of humans

Abstract: A recent study raised concern about increase of resting blood pressure after a 35 min exposure to the radiofrequency (RF) field emitted by a 900 MHz cellular phone. In this randomized, double blind, placebo controlled crossover trial, 32 healthy subjects were submitted to 900 MHz (2 W), 1800 MHz (1 W) cellular phone exposure, and to sham exposure in separate sessions. Arterial blood pressure (arm cuff method) and heart rate were measured during and after the 35 min RF and sham exposure sessions. We evaluated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
43
0
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 16 publications
12
43
0
3
Order By: Relevance
“…The effects of cell phones on the cardiovascular system have been investigated by various researchers by examining parameters such as heart rate and blood pressure but the study results are controversial (13,14). To the best of our knowledge, the effects of exposure to EF on hemorheological parameters have not been studied before.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of cell phones on the cardiovascular system have been investigated by various researchers by examining parameters such as heart rate and blood pressure but the study results are controversial (13,14). To the best of our knowledge, the effects of exposure to EF on hemorheological parameters have not been studied before.…”
Section: Introductionmentioning
confidence: 99%
“…Ancak, gruplarda yer alan deneklerin çoğunda periyotlar arasında görü-len aynı yönlü küçük değişimler, eşleştirilmiş karşılaştırmaların anlamlı fark üretmesine neden olmuştur. Literatürde yer alan çalışmaların bazılarında, CT'den kaynaklanan radyasyona bağlı olarak KHD parametrelerinde değişimler oluşmadığı (7)(8)(9)(10), bazılarında ise oluştuğu belirtilmiştir (11)(12)(13). Bu çalışmalardan sadece Andrzejak ve ark.…”
Section: Discussionunclassified
“…Literatürde, cep telefonlarının (CT) kardiyak otonomik aktivite üzerindeki etkisini, KHD analizlerini kullanarak inceleyen çalışma-lar mevcuttur (7)(8)(9)(10)(11)(12)(13). Bu çalışmalardan elde edilen sonuçlara bakıldığında, birbirleriyle çelişmekte oldukları görülmektedir.…”
Section: Introductionunclassified
“…Of three published studies on the effects of GSM exposure on HR, two found no effect [Braune et al, 2002;Tahvanainen et al, 2004], while one showed a small reduction in HR [Huber et al, 2003]. No effects were found in two studies using UMTS exposure [Eltiti et al, 2007[Eltiti et al, , 2009.…”
Section: Introductionmentioning
confidence: 93%
“…This increased HR indicates that the subjects relaxed less. A GSM study by Huber et al [2003] showed a reduction in HR during waking and stage 1 sleep, whereas, Braune et al [2002] and Tahvanainen et al [2004] found no effect of GSM-EMF on the HR in randomized crossover trials. In contrast to our results, Eltiti et al [2007Eltiti et al [ , 2009 did not find an effect on HR using a base station-like UMTS signal, which had a different carrier frequency of 2020 MHz and was continuous.…”
Section: Medium-term Changesmentioning
confidence: 98%